A quantitative analysis of artificial intelligence research in cervical cancer: a bibliometric approach utilizing CiteSpace and VOSviewer - Zhao, Ziqi; Hu, Boqian; Xu, Kun; Jiang, Yizhuo; Xu, Xisheng; Liu, Yuliang (Frontiers in Oncology, 2024)
BackgroundCervical cancer, a severe threat to women’s health, is experiencing a global increase in incidence, notably among younger demographics. With artificial intelligence (AI) making strides, its integration into medical research is expanding, particularly in cervical cancer studies. This bibliometric study aims to evaluate AI’s role, highlighting research trends and potential future directions in the field.MethodsThis study systematically retrieved literature from the Web of Science Core Collection (WoSCC), employing VOSviewer and CiteSpace for analysis. This included examining collaborations and keyword co-occurrences, with a focus on the relationship between citing and cited journals and authors. A burst ranking analysis identified research hotspots based on citation frequency.ResultsThe study analyzed 927 articles from 2008 to 2024 by 5,299 authors across 81 regions. China, the U.S., and India were the top contributors, with key institutions like the Chinese Academy of Sciences and the NIH leading in publications. Schiffman, Mark, featured among the top authors, while Jemal, A, was the most cited. ‘Diagnostics’ and ‘IEEE Access’ stood out for publication volume and citation impact, respectively. Keywords such as ‘cervical cancer,’ ‘deep learning,’ ‘classification,’ and ‘machine learning’ were dominant. The most cited article was by Berner, ES; et al., published in 2008.ConclusionsAI’s application in cervical cancer research is expanding, with a growing scholarly community. The study suggests that AI, especially deep learning and machine learning, will remain a key research area, focusing on improving diagnostics and treatment. There is a need for increased international collaboration to maximize AI’s potential in advancing cervical cancer research and patient care.